Aging affects B‐cell antigen receptor repertoire diversity in primary and secondary lymphoid tissues. Issue 2 (20th December 2015) - Tabibian‐Keissar, Hilla; Hazanov, Lena; Schiby, Ginette; Rosenthal, Noemie; Rakovsky, Aviya; Michaeli, Miri; Shahaf, Gitit Lavy; Pickman, Yishai; Rosenblatt, Kinneret; Melamed, Doron; Dunn‐Walters, Deborah; Mehr, Ramit; et al.
Abstract : The elderly immune system is characterized by reduced responses to infections and vaccines, and an increase in the incidence of autoimmune diseases and cancer. Age‐related deficits in the immune system may be caused by peripheral homeostatic pressures that limit bone marrow B‐cell production or migration to the peripheral lymphoid tissues. Studies of peripheral blood B‐cell receptor spectratypes have shown that those of the elderly are characterized by reduced diversity, which is correlated with poor health status. In the present study, we performed for the first time high‐throughput sequencing of immunoglobulin genes from archived biopsy samples of primary and secondary lymphoid tissues in old (74 ± 7 years old, range 61—89) versus young (24 ± 5 years old, range 18–45) individuals, analyzed repertoire diversities and compared these to results in peripheral blood. We found reduced repertoire diversity in peripheral blood and lymph node repertoires from old people, while in the old spleen samples the diversity was larger than in the young. There were no differences in somatic hypermutation characteristics between age groups. These results support the hypothesis that age‐related immune frailty stems from altered B‐cell homeostasis leading to narrower memory B‐cell repertoires, rather than changes in somatic hypermutation mechanisms.